2015
DOI: 10.1080/09168451.2015.1010478
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic activity of rosmarinic acid esters is modulated by hydrophobicity, and bulkiness of alkyl side chain

Abstract: Methyl, propyl and hexyl esters of rosmarinic, caffeic and p-coumaric acids were tested for antiallergic activity, and rosmarinic acid propyl ester exhibited the greatest β-hexosaminidase release suppression (IC50, 23.7 μM). Quadratic correlations between pIC50 and cLogP (r(2) = 0.94, 0.98, and 1.00, respectively) were observed in each acid ester series. The antiallergic activity is modulated by hydrophobicity, and alkyl chain bulkiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Additionally, here we evaluated the anti-tumor effects and mechanisms of action of RAME that were not observed after RA treatment (Additional file 1: Figure S6). Interestingly, there are several medicinal chemistry data demonstrating that the length of the alkyl side chain determines the bioactivity of RA derivatives [5254]. According to our virtual screening data in Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, here we evaluated the anti-tumor effects and mechanisms of action of RAME that were not observed after RA treatment (Additional file 1: Figure S6). Interestingly, there are several medicinal chemistry data demonstrating that the length of the alkyl side chain determines the bioactivity of RA derivatives [5254]. According to our virtual screening data in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Rosmarinic acid (RA) is a natural polyphenolic substance found in various Lamiaceae herbs such as perilla [43], rosemary [44], sage [45], mint [46], basil [47], and thyme [48]. A number of studies have reported the biological effects of RA and one of its derivatives RAME, including anti-inflammatory [49, 50], anti-allergic [51, 52], and anti-microbial [53] effects. Additionally, here we evaluated the anti-tumor effects and mechanisms of action of RAME that were not observed after RA treatment (Additional file 1: Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…We observe that modification of the n-propyl radical ( 3 ) to isopropyl ( 4 ) contributes to a reduction in activity, possibly due to the volume of the isopropyl group that compound 4 presents in its branch. Propyl p -coumarate ( 3 ) was twice as potent as 2-methoxyethyl p -coumarate ( 5 ) [42,43]. Compound 3 also presented greater selectivity than compound 5 for the epimastigote form (SI = 26.55, SI ≥ 14.05, respectively), and the trypomastigote form (SI = 3.8, SI ≥ 1.25, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Rosmarinic acid methyl ester (RAME), a derivative of rosmarinic acid (RA), has several biological effects, such as anti-microbial, anti-inflammatory, and anti-allergic effects [ 16 , 17 , 18 ]. RAME also exhibits anti-oxidant and anti-melanogenesis in vivo [ 19 ].…”
Section: Introductionmentioning
confidence: 99%